THE MAHANUBHAVAS AND SCRIPTURE - Anne Feldhaus (Journal of Dharma, 1978)
In the past few years, attempts have been made to interpret medieval Indian bhakti movements in terms of "structure" and "anti-structure," categories introduced by Victor Turner in The Ritual Process.’ Bhakti movements would seem to be ideal candidates for interpretation as anti-structure. In their search for direct experience of God, they assert the equality of all seekers and suspend the rules and hierarchy of orthodox Hinduism. Two works which pursue this line of thought are A.K. Ramanuja’s introduction to his striking translations of Virasaiva’ poetry, and Turner’s own "Metaphors of Anti -structure in Religious Culture," an article which is in part a response to Ramanuja’s work. For interpreting bhakti, these two works taken together suggest extending Turner’s original thesis in at least two ways: first, by adding the category "counter-structure" to the pair "structure" and "anti-structure;" and, second, by extending the meaning of "structure" beyond the sense in which Turner originally intended it.